Empirical Evaluation of Long Waves of Capitalist Development. Issue 2 (2nd July 2020) - Johnson, Nathan
Abstract : The Great Recession was followed by tepid recovery which has stretched into more than a decade of constricted growth. Long wave theory, which aims to elucidate patterns of capitalist development for timeframes beyond the business cycle, is relevant for contextualizing the ongoing extended period of constricted growth. Empirical data for the UK and US, typically spanning the 1800s to the present, are evaluated to ascertain long waves of capitalist development are demonstrable. Several indicators are assessed, including manufacturing and industrial production, GDP, investment, capital formation, exports and imports, unemployment rates, and profitability. Results indicate long waves date from the crisis of free competition capitalism and are most pronounced for periods throughout 1914–1991. Widespread capitalist restoration distinguishes 1992–2007 as an intervening period of qualified capitalist growth, during which China's economy grew dramatically, post-Soviet states struggled, US growth moderately revived, and EU and OECD growth continued to decline. Impacts of the coinciding information and communications technology revolution are also appraised, focusing on the US. Selected indicators are assessed for capitalist-restoration economies and established capitalist aggregate economies in recent long waves. Results do not support the 'long cycle' interpretation of long wave theory, which claims extended periods of economic growth occur cyclically owing to endogenous factors. Instead the interpretation promoted by Ernest Mandel is borne out, which asserts transitions from long waves of robust growth to constricted growth are chiefly the result of endogenous factors while upturns depend upon adequate exogenous socio-political system shocks and technological revolutions. Prospects for future technological revolutions and system shocks are briefly considered.